2018
DOI: 10.1002/adma.201800367
|View full text |Cite
|
Sign up to set email alerts
|

Optically Unraveling the Edge Chirality‐Dependent Band Structure and Plasmon Damping in Graphene Edges

Abstract: The nontrivial topological origin and pseudospinorial character of electron wavefunctions make edge states possess unusual electronic properties. Twenty years ago, the tight-binding model calculation predicted that zigzag termination of 2D sheets of carbon atoms have peculiar edge states, which show potential application in spintronics and modern information technologies. Although scanning probe microscopy is employed to capture this phenomenon, the experimental demonstration of its optical response remains ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
0
12
1
1
Order By: Relevance
“…Secondly, previous studies have shown that next to the zigzag edge, there exists a small region with larger conductivity than that within the graphene flake, which therefore results in a strip of enhanced near-field amplitude, that is, a rim structure. [22,31] However, in our current study it is found that the near-field amplitude distributions close to the two edges are similar. Absence of the rim structure suggests that there is little difference between the optical conductivities for regions near the graphene zigzag and armchair edges.…”
Section: Resultscontrasting
confidence: 44%
See 2 more Smart Citations
“…Secondly, previous studies have shown that next to the zigzag edge, there exists a small region with larger conductivity than that within the graphene flake, which therefore results in a strip of enhanced near-field amplitude, that is, a rim structure. [22,31] However, in our current study it is found that the near-field amplitude distributions close to the two edges are similar. Absence of the rim structure suggests that there is little difference between the optical conductivities for regions near the graphene zigzag and armchair edges.…”
Section: Resultscontrasting
confidence: 44%
“…[20,21] These characteristics are anticipated to endow the 1D edge plasmon modes with topology-specific behaviors that are not observed in the sheet modes. [22] Moreover, the evolution of the edge plasmon modes in response to external stimuli, such as electrical gating, chemical doping, and magnetic field, can in turn help reveal the fine electronic structure at these two edges. A few studies have identified that plasmon behaviors associated with these two edges are different because of the edge-specific electronic band structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For pristine GPs, the relationship between wavelength and doping is described by the following scaling law: λnormalpEnormalFn which can be derived from a general relationship between 2D plasmons and 2D material conductivity, q p (ω) = [ iω (1 + ε sub (ω))]/4 πσ (ω), and the relationship between graphene conductivity σ and the Fermi level E F , σ(ω)=iπ[D/(ω+iτ1)], and D = ( e 2 /πℏ 2 ) E F , where D is the Drude weight. Combining them together, we get the famous relationship between a GP wavelength and the carrier density λnormalpω=8πe2vnormalFπnω21+ϵnormalsubω where v F ≈ c /300 ≈ 10 6 m s −1 is the Fermi velocity 16b,22. Equation tells us thatλnormalpn, indicating that the wavelength λ p changes sensitively with the carrier concentration n .…”
Section: Scaling Behaviors Of the Polariton Wavelength In Low‐dimensimentioning
confidence: 99%
“…[ 1–5 ] Graphene as a promising candidate has been intensively researched due to its unusual electro‐optical properties. [ 6–17 ] To date, various methods have been adopted to design the modulator with high efficiency, including large chemical doping, [ 18–20 ] coupling with an additional resonator, [ 21–24 ] and integrating with Salisbury screens (consisting of a single reflective mirror). [ 25–30 ] However, those methods also have some limitations.…”
Section: Introductionmentioning
confidence: 99%